Synchronization of the Marriage Dispensation Process for Underage Couples According to Lampung Saibatin Custom with Law Number 16 of 2019 - Sulis Tiyawati; Annikmah Farida (Jurnal Mahkamah : Kajian Ilmu Hukum dan Hukum Islam, 2024)
Amendments to Law Number 16 of 2019 which set the minimum age of marriage to 19 years old aim to strengthen child protection through the marriage dispensation mechanism. However, the implementation of these provisions still faces challenges for customary law communities that have their own social legitimacy system. This study aims to analyze the practice of child marriage in the indigenous people of Lampung Saibatin in Marga Ngaras, West Coast Regency, and to examine the level of synchronization of the marriage dispensation mechanism with the provisions of national law. The research uses an empirical juridical approach with qualitative methods through in-depth interviews, observations, and documentation of traditional leaders, the Head of the Office of Religious Affairs, and couples who are married underage. The results showed that of the eight cases of child marriage found, only one couple went through the marriage dispensation procedure through the Religious Court, while the other seven couples carried out the marriage based on customary and religious legitimacy without going through formal legal mechanisms. These findings show that the social legitimacy built by customary authorities is still more dominant than the legality of the state, causing inconsistency in the implementation of Law Number 16 of 2019. The novelty of this research lies in the formulation of a procedural synchronization model that integrates the role of traditional leaders, the Office of Religious Affairs, and the Religious Court in the marriage dispensation process as an effort to harmonize between customary law and national law. The model is expected to strengthen child protection without ignoring the cultural values that live in indigenous peoples.